Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic) - Pestana, Rosa; Ribeiro, Cláudia; Boury-Esnault, Nicole; Biscoito, Manuel (Zootaxa, 2018)
Few surveys on benthic fauna have been performed on the island of Madeira (Alves et al. 2003 and references therein), and the first sponge specimens were collected opportunistically (Johnson 1863, 1899; Topsent 1904, 1928). Porifera can be considered one of the least studied phyla in the Madeira archipelago, within the Lusitanian province. This is not the case for other regions as the Mediterranean (Boury-Esnault 1971 and references therein), Alboran Sea (Carballo 1994), Canary Islands (Cruz 2002), and the Azores (Topsent 1904; Boury-Esnault & Lopes 1985; Xavier 2009), where sponges have been more thoroughly studied.